Association of continuity of carer and women's experiences of maternity care during the COVID-19 pandemic: A cross-sectional survey. (September 2022) - Cummins, Allison; Sheehy, Annabel; Taylor, Jan; Smith, Sally De-Vitry; Nightingale, Ms. Helen; Davis, Deborah
Abstract : Background: Recent research highlights the impact of the COVID-19 pandemic on maternity services, although none to date have asked women how they feel about the changes to care or analysed the association between continuity of carer and women's experiences. Aim: The aim of our research was to discover pregnant women's self-reported changes to their planned care and associations between continuity of carer and how women felt about changes to their planned care. Methods: A cross-sectional online survey of pregnant women aged over 18 years in their final trimester of pregnancy in Australia was undertaken. Results: 1668 women completed the survey. Most women reported at least one change to pregnancy care and birthing plans. Women receiving full continuity of carer were more likely to rate the changes to care as positive (p<0.001) when compared with women who received partial or no continuity. Conclusions: Pregnant women experienced many changes to their planned pregnancy and birth care during the COVID-19 pandemic. Women who received full continuity of carer experienced fewer changes to care and were more likely to feel positive about the changes than women who did not receive full continuity of carer. Our study demonstrates that women are better together through continuity of carer models.